2017
DOI: 10.1007/s11010-017-3159-x
|View full text |Cite
|
Sign up to set email alerts
|

Eryptosis and oxidative damage in hypertensive and dyslipidemic patients

Abstract: Arterial hypertension is a disease that often coexists with dyslipidemia. Both disorders can produce oxidative stress. Studies in vivo and in vitro have proven that oxidative stress can induce an increment of the erythrocyte apoptosis (eryptosis), through the rise of free intracellular calcium concentration ([Ca]). Higher levels of eryptosis have not been described in patients with hypertension, dyslipidemia, or both combined. This study involved 81 men between 26 and 50 years old, assorted into four groups: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 55 publications
2
34
1
Order By: Relevance
“…Both arterial hypertension and dyslipidemia are known to generate oxidative stress. Accordingly, it was previously shown that hypertensive and/or dyslipidemic individuals had 30% lower GSH levels and a doubling of mean lipid peroxidation than normotensive patients without dyslipidemia (Fig. ).…”
Section: Clinical Conditions Stimulating Eryptosis By Generation Of Omentioning
confidence: 76%
See 2 more Smart Citations
“…Both arterial hypertension and dyslipidemia are known to generate oxidative stress. Accordingly, it was previously shown that hypertensive and/or dyslipidemic individuals had 30% lower GSH levels and a doubling of mean lipid peroxidation than normotensive patients without dyslipidemia (Fig. ).…”
Section: Clinical Conditions Stimulating Eryptosis By Generation Of Omentioning
confidence: 76%
“…). Taken together, these observations indicate that both hypertension and dyslipidemia, either alone or concomitantly, generate an increased amount of oxidative stress, although no additive effect of either condition has been observed . As oxidative stress is known to activate Ca 2+ permeable cation channels leading to Ca 2+ entry, hypertensive patients had a 100% and 200% higher mean [Ca 2+ ] i without and with dyslipidemia, respectively.…”
Section: Clinical Conditions Stimulating Eryptosis By Generation Of Omentioning
confidence: 79%
See 1 more Smart Citation
“…Several inbitors of eryptosis have been identified [88][89][90][91]. Eryptosis is enhanced in several clinical conditions including iron deficiency [33], dehydration [33], hyperphosphatemia [33], vitamin D excess [33], chronic kidney disease (CKD) [92][93][94][95][96][97], hemolytic-uremic syndrome [98], autoimmune hemolytic anemia [99], diabetes [33], hypertension and dyslipidemia [100], hepatic failure [101], malignancy [102][103][104], arteritis [105], systemic lupus erythematosus [106], sepsis [107,108], malaria [33,109,110], sickle-cell disease [33], beta-thalassemia [33], Hb-C and G6PD-deficiency [33], Wilsons disease [107], as well as advanced age [33]. Eryptosis is fostered by storage for transfusion [41,42,58,111].…”
Section: Introductionmentioning
confidence: 99%
“…Several substances inhibit eryptosis [113][114][115][116]. Enhanced eryptosis is observed in diverse clinical conditions including iron deficiency [58], vitamin D excess [117], chronic kidney disease (CKD) [118][119][120][121][122][123], hemolytic-uremic syndrome [124], autoimmune hemolytic anemia [125], diabetes [126], hypertension and dyslipidemia [127], hepatic failure [128], malignancy [129][130][131], arteritis [132], systemic lupus erythematosus [133], sepsis [134,135], malaria [58,136,137], sicklecell disease [58], beta-thalassemia [58], Hb-C and G6PD-deficiency [58], Wilsons disease [134], as well as advanced age [138]. Eryptosis further increases following storage for transfusion [67,68,83,139] and is enhanced in erythrocytes from newborns exposed to oxidative stress [58,140].…”
Section: Introductionmentioning
confidence: 99%